Time-Driven Activity Based Costing: An Innovative Method for Calculating the Cost of Renting a Hall in a Public Service Agency (BLU) - MEIDINA, Audy; LESTARI, Utami Puji (Journal of Governance, Taxation and Auditing, 2025)
Determining rental rates for building facilities requires an accurate method that accommodates the actual activities and resources involved. Time-Driven Activity-Based Costing (TDABC) is considered an innovative method for calculating the cost of service rentals. This study aims to analyze the application of the TDABC method in determining the service cost of hall rentals at PTN-BLU X. Until now, PTN-BLU X has used a traditional method that merely compares the rental rates of other buildings without considering actual activities and resource usage, which can potentially lead to cost distortion. This research employs a descriptive qualitative approach with data collection techniques such as semi-structured interviews, unstructured observations, and documentation. The analysis is conducted by calculating and comparing service costs using both traditional and TDABC methods. The findings reveal that the TDABC method can identify activities, activity time, practical capacity, and unused activity costs in a more detailed manner. This method provides more accurate cost calculations and reflects actual resource consumption for each type of activity, such as seminars, training sessions, and school graduation ceremonies. The application of TDABC can serve as a more realistic basis for setting rental rates and support more effective managerial decision-making within PTN-BLU X.